Mixed signals: cognitive skills, qualifications and earnings in an international comparative perspective. (2nd January 2020) - Shields, Robin; Sandoval Hernandez, Andres
ABSTRACT: The relative importance of educational qualifications and cognitive skills forms an enduring debate in research on education and the labour market. While early work in human capital theory essentially equated qualifications and skills, signalling and screening theories provided a more nuanced distinction between the two, highlighting the importance of qualifications as a way of reducing uncertainty in hiring. Recent literature argues that most formal education is largely signalling that provides minimal productivity gains. This paper seeks to inform the debate on human capital and signalling theories by examining cross-national variation in how the qualifications and cognitive skills relate to earnings. Using data from the Programme for the International Assessment of Adult Competencies (PIAAC), we analyse variation in how cognitive skills (literacy, numeracy and problem-solving) and qualifications (secondary and higher education completion) relate to earnings. Although the contributions of qualifications tend to outweigh cognitive skills, the relative contributions of each factor vary considerably across countries. This variation suggests that high levels of signalling are not inevitable and may be explained by contextual differences in education systems and labour markets. Countries with more higher education attainment have lower levels of signalling and place higher premiums on cognitive skills.